‚Jeg’ (det) er en anekdote: Talens gestus i samtidsteatret - Naumann, Matthias (Peripeti, 2021)
In his analysis of Ohad Naharins Virus (Batsheva Dance Company, 2001), Bloody Mess (Forced Entertainment, 2004), and Stadt als Beute (René Pollesch, Volksbühne im Prater, 2001), Matthias Naumann writes about the gesture of speech in contemporary theatre.